WORKSHOP PENDIDIKAN SEBAGAI UPAYA MEMBANGUN LITERASI SAINS DI WILAYAH JATINEGARA KAUM - Ferdiansyah Faturachman Achmad; Febriana Yunhas Putri; Marliana Candra Kartika; Rania Virda Sukmaningsih; Ridha Octa Alhuriyyah Azzahra; Iwan Sugihartono; Jaja Jamaludin; Achmad Ainul Yaqin; Jack Luhukay (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
AbstractBased on the 2018 Programme for International Student Assessment (PISA) report, Indonesia received an average PISA index score of 396 in the field of science and was ranked 71st out of 79 countries. It proves that the scientific literacy skills of Indonesian children need to be improved. Therefore, the Team of Community Service Integrated Kuliah Kerja Nyata (KKN) of the State University of Jakarta held a workshop for elementary school teachers in the Jatinegara Kaum with the topic